2019
DOI: 10.3389/fimmu.2019.02686
|View full text |Cite
|
Sign up to set email alerts
|

The Balance in T Follicular Helper Cell Subsets Is Altered in Neuromyelitis Optica Spectrum Disorder Patients and Restored by Rituximab

Abstract: Neuromyelitis optica spectrum disorder (NMOSD) is a rare and severe auto-immune disease of the central nervous system driven by pathogenic antibodies mainly directed against aquaporin-4 (AQP4-Ab). Treatment of NMOSD currently relies on immunosuppressants (mycophenolate mofetil, azathioprine) or B-cell-depleting therapy (rituximab). B-cell differentiation into antibody-producing cells requires T follicular helper cells (Tfh). There are several Tfh subsets that differentially affect B-cell differentiation; Tfh2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Neuromyelitis optica spectrum disorders (NMOSD) are also inflammatory demyelinating diseases affecting CNS, characterized by presence of anti auqaporin-4 antibodies [85]. Multiple studies showed increased frequencies of cTfh cells in NMOSD patients [86][87][88]. They had correlation with disease activity and treatment with methylprednisolone led to a significant decrease of cTfh cells frequency [87].…”
Section: Neuroinflammatory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuromyelitis optica spectrum disorders (NMOSD) are also inflammatory demyelinating diseases affecting CNS, characterized by presence of anti auqaporin-4 antibodies [85]. Multiple studies showed increased frequencies of cTfh cells in NMOSD patients [86][87][88]. They had correlation with disease activity and treatment with methylprednisolone led to a significant decrease of cTfh cells frequency [87].…”
Section: Neuroinflammatory Diseasesmentioning
confidence: 99%
“…They had correlation with disease activity and treatment with methylprednisolone led to a significant decrease of cTfh cells frequency [87]. Untreated NMOSD patients showed an imbalance of cTfh subsets: increase of cTfh17 and (cTfh2 þ cTfh17)/cTfh1 ratio [88]. Of interest, anti-CD20 antibody, rituximab, altered the Tfh polarization to that of healthy controls [88].…”
Section: Neuroinflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicolas et al . reported that elevated cTfh cells can be reverted in patients with neuromyelitis optica after treatment with rituximab [43], suggesting exploring new therapeutic solutions for MS.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a murine model of post-infection associated autoimmunity, reactive T cells migrate from the periphery into the CNS and contribute to neuroinflammation. [26][27][28] Indeed, a dysregulated T-cell compartment has been described in other neuroinflammatory disorders, most notably in multiple sclerosis (MS), [29][30][31] but also in neuromyelitis optica spectrum disorders (NMOSDs), [32][33][34] Rasmussen's encephalitis 35,36 and paraneoplastic syndromes. 37,38 In this study, we report on the presence of peripheral autoreactive T cells against D2R in paediatric patients with movement and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%